Resíduos produzidos nas feiras abertas da cidade de Manaus como substrato para o cultivo e produção de lacase por Pleurotus ostreatus - Santos, Luana Carolina Rocha Marinho dos (2016)
The aim of this study was to investigate the feasibility of using waste produced in open fairs in the city of Manaus as a substrate for the cultivation and laccase production by Pleurotus ostreatus. For the selection of the more suitable waste for cultivation were performed bioprocesses using tucuma’s peel (Astrocaryum aculeatum), cupuacu’s peel (Theobroma grandiflorum), peach palm’s peel (Bactris gasipaes), acai seed (Euterpe oleracea) and peel of the root of cassava (Manihot esculenta). The residues were obtained from open markets in the city of Manaus and dry in air circulation oven at 70 ° C and used with 20% wheat bran as supplementation. The residues were crushed and standardized, and its moisture corrected to 70% by weight of the mixture. An inoculum was prepared with wheat bran and after incubation it was poured in bags containing residue. After incubation and fruiting mushrooms were harvested and weighed for biological efficiency calculation (EB) and loss of organic matter (PMO). For the investigation of laccase production in the waste samples were taken from the bags containing residue 10,15,20,25 and 30 days and the activity of laccase was determinated. As a result the tucuma’s peel had the highest production of laccase (21766.82 U / kg) followed by the peach palm’s peel (6161.43 U / kg). Peel of the root of cassava showed the highest biological efficiency (12.82%). The peach palm’s peel residue was selected for the optimization step. To this residue were investigated the most appropriate conditions for the cultivation and production of laccase. Using factorial design and response surface was possible to determine the best conditions for the production of laccase by P. ostreatus. Thus, the excellent condition for the production of laccase was using 150g of peach palm’s pell and 60% of moisture where it obtained a laccase production of 3565.02 U / Kg. Keywords: Pleurotus ostreatus, edible mushrooms, laccase production, vegetable waste